Identifikasi Masalah Pada UMKM Kota Padang dan Solusinya Pada Kedai Sala Lauak dan Perkedel Jagung di Depan Kampus UPI ”YPTK” Padang - Mutia Sahilna; Nadia Putri; Neneng Senja Agusta; Nurkhalifah Salsabilla; Vivi Nila Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a form of productive economy that stands alone, meaning that these businesses are not subsidiaries or branches of any company, whether government companies or individual companies. In this research, researchers chose MSMEs located in front of the UPI